PENGARUH PENAMBAHAN SILIKON TERHADAP SUDUT KONTAK HIDROPOBIK DAN KARAKTERISTIK ARUS BOCOR PERMUKAAN BAHAN RESIN EPOKSI - Abdul Syakur; Ika Novia A; Sarjiya Sarjiya; Hamzah Berahim (TEKNIK, 2011)
Currently, polymer materials such as epoxy resin have been used as an insulator in the distribution andtransmission line. Some advantages of using this epoxy resin material having the dielectric properties are betterthan porcelain and glass insulators. On the other side, epoxy resins are also disadvantage the surface ishygroscopic. For the repair was done by adding the surface properties of silicone rubber materialThis paper describes the effect of adding silicone rubber against contact angle of hidrophobicity and surfaceleakage current characteristics of epoxy resin materials ( Di-Glycidyl Ether of Bisphenol A (DGEBA) andMethaphenilene Diamine (MPDA). The study was conducted in the laboratory using the electrode method IEC587:1984 with NH4Cl contaminants. The voltage applied to the epoxy resin sample at 3.5 kV and 50 HzfrequencyThe experimental results showed that the addition of silicon rubber in epoxy resin makes the surface materialcontact angle increases. The higher percentage of silicone rubber, the greater the contact angle and the longertime required for the occurrence of surface discharge.